2020
DOI: 10.3389/fimmu.2020.592721
|View full text |Cite
|
Sign up to set email alerts
|

Robust Production of Merkel Cell Polyomavirus Oncogene Specific T Cells From Healthy Donors for Adoptive Transfer

Abstract: Virus positive Merkel cell carcinoma (VP-MCC) is an aggressive but immunogenic skin malignancy driven by Merkel cell polyomavirus (MCPyV) T antigen (TAg). Since adoptive T cell transfer (ACT) can be effective against virus-driven malignancies, we set out to develop a methodology for generating MCPyV TAg specific T cells. MCPyV is a common, asymptomatic infection and virus-exposed healthy donors represent a potential source of MCPyV TAg specific T cells for ACT. Virus specific T cells were generated using monoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 57 publications
(62 reference statements)
1
4
0
Order By: Relevance
“…However, significant numbers of antigen-specific CD8 T cells were not observed after vaccination with ITI-3000 ( Figure 2D ). This agrees with previous studies using human PBMC and MCC tumor-infiltrating cells that demonstrate strong CD4 T cell-mediated immune responses to the LT antigen ( 16 , 24 , 42 , 43 ).…”
Section: Discussionsupporting
confidence: 92%
“…However, significant numbers of antigen-specific CD8 T cells were not observed after vaccination with ITI-3000 ( Figure 2D ). This agrees with previous studies using human PBMC and MCC tumor-infiltrating cells that demonstrate strong CD4 T cell-mediated immune responses to the LT antigen ( 16 , 24 , 42 , 43 ).…”
Section: Discussionsupporting
confidence: 92%
“…Some studies have revealed that tumor infiltration by Th1 CD4+ T cells, Th2 CD4+ T cells, and Th17 CD4+ T cells can mediate regression of advanced solid tumors. 30 Thus, these evidences provide a potential mechanism of zc3h12d in tumor immune microenvironment for researchers.…”
Section: Discussionmentioning
confidence: 83%
“…This confirmed our expectations since both donor and patient blood are screened on a regular basis. However, traces of Merkel cell polyomavirus, which does have pathogenic potential, were observed in both healthy blood donors and dialysis pools ( Figure 2 ) [ 46 , 47 ]. Furthermore, segments of rotavirus A ( Reoviridae ), a common cause of gastroenteritis in children, [ 48 ] and adenovirus (type 41/F) have been observed in plasma pools of control patients.…”
Section: Discussionmentioning
confidence: 99%